Effects of demographic factors on intention for selfemployment among postgraduate students of Abubakar Tafawa Balewa University, Bauchi-Nigeria - Na-Allah, Shehu Rabiah; Mallo, Mangai Josiah; Bogoro, Patrick (Faculty of Management Studies & Commerce, University of Jaffna, 2018)
High unemployment rate among Nigerian graduates has been the issue of concern to both government and concerned stakeholders in the quest of finding alternative solution to the problem. So the federal government enacted policies and programmes with mandate of providing support to address these problems. Policy trusts like Small and Medium Enterprise Agency of Nigeria, Youth Empowerment Support, Bank of Industry, Bank of Agriculture, Graduate Entrepreneurship Programme, Industrial Training Fund, Youths Enterprise Scheme, etc. were established by various administrations overtime. Yet the search for paid job among graduates still persist. It was against this background that this study examines the effect of demographic factors on intention for self-employment among postgraduate students of Abubakar Tafawa Balewa University, Bauchi-Nigeria. The students cut across six faculties of Engineering, Science, Agriculture, Management, Environmental and Education. Cross-sectional survey research design was used in which 311 questionnaires were administered to respondents using proportionate stratified sampling technique. 309 questionnaires were returned, 5 discarded as outliers and 304 were due for data analysis. The data was analyzed using IBM SPSS software version 23.0. Age, was analyzed using univariate analysis and analysis of variance (ANOVA), while gender was analyzed using independent samples t-test analysis. Finding of the study reveals gender as a significant factor on intention for self-employment with males possessing higher intention than females' counterparts. Therefore, universities should complement government effort by channeling entrepreneurial support to postgraduate students on the basis of gender. Universities should even replicate world-class practice by establishing an innovation-lab where future student-entrepreneurs can be trained early on skills acquisition programmes. This will help reduce graduates' unemployment and bringing about productivity for growth and development of the economy.
Keywords: Demographic factors; Self-employment; Postgraduate student